Nonlinear effects and numerical results in salt transfer problems - Baltabaeva Rano; Djumabaev Kuanishbay; Axmedova Kunduz; Reimova Laura (E3S Web of Conferences)
In this paper, numerical solutions of the nonlinear equations of dust and salt transference processes are considered. The phenomenon of finite propagation velocity, dust disturbances, and groundwater filtration is established on the basis of self-similar analysis and the principle of comparing solutions.